Organometallic routes to colloidal zinc oxide nanoparticles and layered zinc hydroxides - Leung, A (2018)
The thesis focuses on the controlled hydrolysis of organozinc precursors to form colloidal, surface-functionalised, ZnO nanoparticles (2–4 nm) and exfoliated nanosheets of layered zinc hydroxides (3 nm thick), with a primary application in the catalytic hydrogenation of CO2 to methanol. An introduction to the topic and a literature review are provided in Chapter 1. Chapter 2 entails a description of characterisation techniques. Chapter 3 presents the synthesis of layered zinc hydroxides, intercalated with a range of carboxylates (acetate, hexanoate, decanoate, oleate and benzoate). Exfoliation of layered zinc hydroxide into monolayers was achieved by stirring the material intercalated with oleate ligand, in toluene, for 2 h. The dimensions of the nanostructures are 3 nm thick × ~ 26 nm (AFM and TEM). In addition, a nanoporous ZnO film (1 μm thick) was formed after annealing a film of solution-deposited material at 500 °C, for 15 mins. Chapter 4 details the synthesis of ZnO nanoparticles (< 3 nm) by hydrolysis of diethylzinc, with di(octadecyl)phosphinate (5 : 1 Zn/ligand loading) . The use of such ligand halts the solid-state ripening of the nanoparticles. The ZnO nanoparticles, combined with Cu(0) or Cu2O nanoparticles, demonstrate catalytic activity for the hydrogenation of CO2 to methanol, using a liquid-phase continuous flow stirred tank reactor (mesitylene, 210 °C, 50 bar, 3:1 molar ratio of H2:CO2, 150 mL min-1 flow). The colloidal Cu/ZnO nanocatalysts exhibit 2-3 times higher rates when compared to the standard commercial heterogeneous Cu-ZnO-Al2O3 catalyst (~20 vs. 7 mmolMeOH gCuZnO-1 h-1). The use of either Cu(0) or Cu2O nanoparticles results in the same catalytic activity and selectivity, but the use of smaller ZnO nanoparticles results in slightly higher activity. Post-catalysis analysis shows an increase in the oxidative stability of Cu(0) nanoparticles. One explanation may be the migration, under catalytic conditions, of ZnO onto Cu(0) nanoparticles that generates a protective layer against oxidation. Chapter 5 describes the substitutional doping of ZnO nanoparticles, with 5 mol% of Mg(II), Al(III) and Cu(I). Characterisation of electronic properties (UV-Vis, Tauc plot), solid-state structure (XRD) and composition (ICP-OES, XPS) confirms the substitutional doping in all cases. Under the same catalysis conditions outlined in Chapter 4, all the nanocatalysts display higher activity and better stability than the commercial heterogeneous catalyst. Nonetheless, when compared to ZnO, Mg-doping reduces activity, whilst Al-doping increases activity (600 vs. 1020 μmol mmolmetal-1 h-1). Chapter 6 summarises the findings from Chapter 3, 4 and 5, followed by the outlook of these chapters. Finally, the experimental methods are presented in Chapter 7.